Covid-19 Dalam Kerangka Irregular Warfare :dari Perspektif Strategi Pertahanan Negara - Arif Mustofa, Arif Mustofa (Jurnal Keamanan Nasional, 2020)
Threats to national defense basically not only come from the military or physically, but threats also come from non-military and non-physical aspects and even in plain sight. The threat that is currently happening in Indonesia and even in the world today is in the form of an epidemic caused by a virus called Covid-19. The COVID-19 disease outbreak can be classified as a nonmilitary threat in the form of a real threat at present and in the future. Overcoming this threat places government agencies outside the field of defense as the main element supported by other elements of the nation’s power. This article discusses COVID-19 in the framework of non-conventional warfare or irregular warfare in the future. A different national defense strategy is needed if Covid-19 is used by non-state actors within the framework of irregular warfare which has threatened the nation’s sovereignty, integrity, and safety. The strategy is a universal defense strategy involving all components of the nation which is organized by placing the defense element as the main component supported by all other components of the nation. This requires a legal foundation as the basis for its implementation. Indonesia needs to prepare itself to face this irregular warfare in the future.